ANALYSIS OF CUSTOMER SERVICE BUSINESS PROCESS USING DATA MINING - ABDUL RAHIM, NURALIAH (IRC, 2020)
Data mining delivers fact-based insight into how customer service business processes have been executed from the data collected to handle the problems and requests of customers. Unified customer service known as customer self-service or intelligent facilities refers to the managerial effort to technologies and processes to resolved issues for the customers. In this report, data mining as a data analysis tool will be implemented to extract the information and hidden knowledge to enhance the decision-making process for better management of resources. Moreover, the analysis focuses on the current customer service management and how to apply the data mining technology to partitioning problems and determine who is responsible to resolve the problem. Hence, this paper contribute to justify by the basic concepts of data mining, described the selected types and models of algorithms, and the process of data mining by using R Tools.